OVERVIEW OF MICROORGANISM CROSS- CONTAMINATION PREVENTION VIA DOOR HANDLES AT HEALTH CARE CLINIC UTILISING 'TOUCH-LESS CONCEPT DOOR - Nesfu, Nadiah Alwani Mohd; Ulang, Norhidayah Md; Baharum, Faizal (CENTRAL ASIA AND THE CAUCASUS, 2021)
A health care facility is a place where people come to seek treatment when they are ill. Despite essential, the facility also well-known for its un-hygienic environment and potentially leads to health hazards such as healthcare-associated infections (HCAI). HCAI are infections acquired by patients while getting treatment at hospitals or ambulatory surgery centres caused by bacteria, fungi, viruses, or other, less frequent pathogens in the health care facility). Prolonged hospital admissions, increased antibiotic resistance in microorganisms, a substantial rise in the financial load on health care systems, higher treatment expenses for patients and their families, and an increase in mortality are all HCAI’s consequences (ICU, One of the frequent touches surfaces in a health care facility are door handles. Hence, the research is to study the effectiveness of the ‘Touch-less concept door,’ a.k.a TCD; it intends to reduce the microorganism surface contamination and the infection risk. TCD is a simple, cost-effective, and lowtechnology concept approach and does not require tedious maintenance. This door fabricates by the appointed door fabricator, and mounts at CE Room 2, the busiest room in the OPD of Sungai Dua Healthcare Clinic. The efficacy of TCD is determined by comparing microorganism loads at the existing doors in CE Room 1 and CE Room 3. Before TCD installation, five days of surface sampling activity was conduct to determine the existing bacterial condition. The data reveals an average CFU/mL bacteria load of 1.33, 0.63, and 0.35 for CE Room 2, CE Room 3, and CE Room 1, respectively despite the doorknobs are sanitised three times throughout the facility's operation hour. Meanwhile, the after TCD installation data reveals an average CFU/mL of 0.183 and 0.626 for CE Room 1, and CE Room 3. However, the average CFU/mL of bacteria load for CE Room 2 is 0.038 CFU/mL (point A: copper push plate) and 0.098 CFU/mL (point B: samples swabbed within 250mm below the push plate placement). This amount lessens 90 % compared to the CE Room 2 average number of bacteria detected previously. The finding indicated that the introduction of spontaneously antimicrobial surfaces, i.e., copper push plate reduced the microbial cross-contamination on the TCD adding with the push door concept. In summary, the TCD could be an alternative engineering solution to reduce or eliminating microorganism cross-contamination on its animate surface compared to the conventional door. Thus, by mounting the TCD in the health care setting, the HIA potentially be reduced along with the AMR.